Effects of herbage ingestion upon ileal digestibility of amino acids in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R.; Nieto, R.; Aguilera, J. F. (JOURNAL OF ANIMAL PHYSIOLOGY AND ANIMAL NUTRITION, 2010)
P>We conducted two experiments with heavy Iberian pigs to determine the ileal digestibility of amino acids (AA) in acorns and freshly cut herbage, and the effects of adding fresh herbage upon the supply of ileal digestible AA when pigs were fed on holm-oak acorns. In Experiment 1, carried out in cannulated pigs of 107 kg bodyweight (BW), daily intake of acorns reached 44.9 g DM/kg0.75 BW. Arg, His and Thr showed the lowest apparent ileal digestibility (AID) values, whereas Met, the branched-chain AA and Phe had the highest coefficients. The AID of total EAA was 0.716 but only 0.222 for NEAA. Most of the digestive and absorptive processes of acorn protein occurred before the hindgut. Acorn provides (per kg DM) 2.27 g apparent ileal digestible Lys and 22.7 g apparent total digestible AA. Standardized ileal digestibility (SID) values for EAA, NEAA and total AA were 0.924 +/- 0.020, 0.784 +/- 0.041 and 0.860 +/- 0.029. In Experiment 2 fresh herbage was given to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg0.75 BW) or as a supplement to acorns (28.4 g DM/kg0.75 BW). When only freshly cut forage was offered the AID of the EAA, NEAA and total AA was close to 0.65 and supplied (per kg DM ingested) 5.61 g AID Lys and 91.7 g digestible AA. Standardized ileal values were 0.744 +/- 0.023, 0.912 +/- 0.038 and 0.831 +/- 0.030 respectively. The addition of fresh forage to the acorns led to a significant decrease in AID of AA in acorn due to digesta transfer to the hindgut: His (p < 0.01), Met (p < 0.001), Phe (p = 0.092), Thr (p < 0.05) and Val (p < 0.05), but Arg, Lys and the branched-chain AA remained unaffected. The main contribution of herbage to AA nutrition of the grazing Iberian pig relies mainly on increasing the supply of digestible AA for pig tissues.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: acorns; amino acids; digestibility; herbage; iberian pig

Effects of herbage ingestion on the digestion site and nitrogen balance in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R.; Nieto, R.; Lachica, M.; Aguilera, J. F. (LIVESTOCK SCIENCE, 2007)
We conducted two experiments in heavy-weight Iberian pigs to determine: a) the effect of lysine or protein addition - the former as L-lysine-HCl, the latter by fresh cut herbage supplementation - on protein deposition when they were fed on holm-oak acorns; b) the digestibility of energy and nutrients in acorns and freshly cut, mixed herbage; and c) a possible change in the partition of digestion along the gastro-intestinal tract of the pigs fed on acorns with the inclusion of herbage. In Experiment 1, carried out in eight cannulated pigs, the daily intake of acorns reached 44.9 g DM/kg(0.75) BW and the addition of 0.58 g L-lysine/kg of whole acorns failed to alter N retention significantly (P > 0.05). We obtained high coefficients for the apparent total-tract digestibility of dry matter (ApDM(tt), 0.84) and organic matter (ApOM(tt), 0.86) and of gross energy (ApGE(tt), 0.84) in whole acorns. The corresponding ileal values were 0.71, 0.74 and 0.74. The N balance was on average - 1.08 g/day. In Experiment 2, fresh herbage containing principally legumes was offered to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg(0.75) BW) or as a supplement to acorns (28.4 g DM/kg(0.75) BW; in this case the herbage accounted for 22% of the daily DM intake). The apparent ileal digestibilities of OM and GE for herbage accounted for 70 to 77% of the values observed at total-tract level (0.65 and 0.64 respectively). N retention reached 4.21 g/day. Average ApDM(tt), ApOM(tt) and ApGE(tt) in the herbage/whole-acorn mixture were slightly above 0.74. The intake of freshly cut herbage as complementary feed to acorns resulted in a significant transference of digesta from the small intestine to the hind gut together with a substantial decrease in ileal digestibility of nutrients and energy (P < 0.001) and a moderate decline in digestibility at throughout the whole tract (P < 0.01-P < 0.001). On the other hand, the apparent digestibility of total N increased (P < 0.001) and 31% of the N apparently digested was retained in the body of the pigs. We also observed a substantial decrease in the precaecal digestion of the DM (P < 0.01), OM (P < 0.01) and GE (P < 0.05) in acorn kernels. We concluded that the main contribution of herbage to the overall nutrient supply to the grazing Iberian pig would rely upon the provision of amino acid N and also of available minerals, both present in low quantities in acorns. (C) 2007 Elsevier B.V All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: acorns; digestibility; energy value; herbage; iberian pig

Effects of herbage ingestion on the digestion site and nitrogen balance in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R; Nieto, R; Lachica, M; Aguilera, J F (LIVESTOCK SCIENCE, 2007)
We conducted two experiments in heavy-weight Iberian pigs to determine: a) the effect of lysine or protein addition - the former as L-lysine-HCl, the latter by fresh cut herbage supplementation - on protein deposition when they were fed on holm-oak acorns; b) the digestibility of energy and nutrients in acorns and freshly cut, mixed herbage; and c) a possible change in the partition of digestion along the gastro-intestinal tract of the pigs fed on acorns with the inclusion of herbage. In Experiment 1, carried out in eight cannulated pigs, the daily intake of acorns reached 44.9 g DM/kg(0.75) BW and the addition of 0.58 g L-lysine/kg of whole acorns failed to alter N retention significantly (P > 0.05). We obtained high coefficients for the apparent total-tract digestibility of dry matter (ApDM(tt), 0.84) and organic matter (ApOM(tt), 0.86) and of gross energy (ApGE(tt), 0.84) in whole acorns. The corresponding ileal values were 0.71, 0.74 and 0.74. The N balance was on average - 1.08 g/day. In Experiment 2, fresh herbage containing principally legumes was offered to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg(0.75) BW) or as a supplement to acorns (28.4 g DM/kg(0.75) BW; in this case the herbage accounted for 22% of the daily DM intake). The apparent ileal digestibilities of OM and GE for herbage accounted for 70 to 77% of the values observed at total-tract level (0.65 and 0.64 respectively). N retention reached 4.21 g/day. Average ApDM(tt), ApOM(tt) and ApGE(tt) in the herbage/whole-acorn mixture were slightly above 0.74. The intake of freshly cut herbage as complementary feed to acorns resulted in a significant transference of digesta from the small intestine to the hind gut together with a substantial decrease in ileal digestibility of nutrients and energy (P < 0.001) and a moderate decline in digestibility at throughout the whole tract (P < 0.01-P < 0.001). On the other hand, the apparent digestibility of total N increased (P < 0.001) and 31% of the N apparently digested was retained in the body of the pigs. We also observed a substantial decrease in the precaecal digestion of the DM (P < 0.01), OM (P < 0.01) and GE (P < 0.05) in acorn kernels. We concluded that the main contribution of herbage to the overall nutrient supply to the grazing Iberian pig would rely upon the provision of amino acid N and also of available minerals, both present in low quantities in acorns. (C) 2007 Elsevier B.V All rights reserved.
Keywords: acorns; digestibility; energy value; herbage; iberian pig